Regulation and Protection of the Sea from Oil Pollution by Tanker Ships in Indonesia - Elly Kristiani Purwendah; Aniek Periani; Elisabet Pudyastiwi (Universitas Pendidikan Ganesha, 2021)
Environmental control in this case is intended to include prevention, mitigation and recovery carried out by the government, regional government and those in charge of businesses and/or activities in accordance with their respective authorities, roles and responsibilities. One of the instruments for preventing pollution and/or environmental damage consists of; environmental economic instruments, environmental-based laws and regulations, environmental-based budgets and other instruments according to the needs and/or developments of science.